The legal status of the person in "The mitayo" González Prada - Rodríguez Chávez, Iván (2021)
This paper analyses the legal/juridical content found in the lyrical poem El mitayo relating the person's legal status which is presented through people's inequality before the law and its branches: unequal opportunities, access to property and freedom to contract. It is also worth noting the relationship between the blanco (the master) and the mitayo (the "indio"), subjected to a regime of exploitation.The analysis of this poem reveals the political intention that González Prada develops rationally in the essay and now, successfully, in Poetry. He accents the sentimental and emotional as an ideal resource for the communication's branch in charge of the text's form.